Haute couture: molecules and biocatalysts - Abdul Rahman, Mohd Basyaruddin (Universiti Putra Malaysia Press, 2010)
For the next 50 years, chemistry will be just as fashionable as it has been in the past 50 years. In fact, the role of chemistry is bigger than ever with the help of bioinformatics that are riding the waves of genomic revolution. Bio-based processes and entities are becoming more organic with civilians requesting sustainable approaches to everything. Globally, the runway for the implementation of industrial biotechnology is nearly complete and is ready to overtake harsh chemical processes. However, major issues such as the high capital costs of advanced biocatalysts, organic solvent replacements and bioreactor technologies are the winding roads to progress. Research on enzymes and liquid engineering has brought us to new dimensions of understanding the unknown capabilities of unnatural enzyme systems at the molecular and atomic levels. The development of designer biocatalysts for industrial purposes to substitute traditional processes is gaining interest. Utilisation of local microbial enzymes and our tropical biodiversity for the discovery and identification of new biocatalysts through advanced structural and synthetic biology are the key focuses. In addition, bioinformatics or the in silico approach of designing novel single molecules to macromolecules is a powerful tool to model any mechanism and structure. By all accounts, the efficient use of bio-renewable resources requires blending different systems of chemistry and biology; heterogeneous and homogeneous, enzymes and metals, microbial and yeast, etc. This technology presents current and potential areas in which the use of a biocatalyst is a prerequisite for an economical application in green organic syntheses. Considering the industrial importance of the platform and fine chemicals, the optimal conditions for up scaling the process are evaluated by statistical methods while taking into consideration, all of the sustainable, environmental and economical evaluations. It will be essential for chemists or biological engineers to design and model the biocatalysts to significantly guide and quicken the steps for synthesising new molecules and improve existing systems. We need many new revolutionary molecules and biocatalysts for a plethora of chemical reactions and industrial applications.